(Mis)aligning politicians and admirals: The problems of long‐term procurement in the Canadian Surface Combatant project 1994‐2021. (12th February 2022) - Migone, Andrea; Howlett, Alexander; Howlett, Michael
Abstract: Popular depictions of the largest single procurement project in Canadian history—the Canadian Surface Combatant (CSC) project—characterize it as a bureaucratic failure. What began in 2008 as a 26.2B project has expanded to at least 77.3B, and 2B has already been spent without having produced a single vessel. Unlike other major Canadian aircraft, helicopter, and submarine contracts over the past four decades, however, participants in the CSC have lauded the technical merits of the procurement process. This article argues that successful procurement in this area requires: (a) clear (naval) doctrine supporting why a specific (weapons) platform or system is needed; and (b) government acceptance of that doctrine. When these two imperatives are aligned, procurement should proceed relatively smoothly. However, such smooth procurement is highly unlikely when major systems purchases involve long time periods and shifts in elected governments, policy goals, or (naval) doctrine undermine previous understandings and agreements. Sommaire: Le plus grand projet d'approvisionnement de l'histoire du Canada – le projet de Navires de combat canadiens (NCC) – est décrit comme un échec bureaucratique par les représentations populaires. Ce qui a commencé en 2008 comme un projet de 26, 2 milliards s'est étendu à au moins 77, 3 milliards , et 2 milliards ont déjà été dépensés sans avoir encore produit un seul navire. Contrairement à d'autres gros contrats canadiens d'avions, d'hélicoptères et de sous‐marins au cours des quatre dernières décennies, les participants au NCC ont néanmoins fait l'éloge des avantages techniques du processus d'acquisition. Cet article soutient qu'un approvisionnement réussi dans ce domaine exige : (a) une doctrine (navale) claire expliquant pourquoi une plate‐forme ou un système (d'armes) spécifique est requis; et (b) l'acceptation de cette doctrine par le gouvernement. Lorsque ces deux impératifs sont alignés, la passation des marchés publics devrait se dérouler de manière relativement fluide. Cependant, un telle fluidité d'approvisionnement est hautement improbable lorsque les achats de systèmes majeurs impliquent de longues durées et lorsque les réorientations des gouvernements élus, des objectifs stratégiques ou de la doctrine (navale) discréditent les ententes et accords antérieurs.